The synoptic problem: a way through the maze - Goodacre, Mark S. (The biblical seminar, 2001)
A lively, readable and up-to-date guide to the Synoptic Problem, ideal for undergraduate students. Arguably the greatest literary enigma in history, the Synoptic Problem has fascinated generations of scholars who have puzzled over the agreements, the disagreements, the variations, and the peculiarities of the relationship between the first three of our canonical Gospels. Yet the Synoptic Problem remains inaccessible to students, soon tangled up in its apparent complexities. But now the author offers a way through the maze, with the promise of emergence at the end, explaining in a lively and refreshing style what study of the Synoptic Problem involves, why it is important and how it might be solved. This is a readable, balance and up-to-date guide, ideal for undergraduate students and the general reader.